Influence of orientation relationship between ferrite and cementite in pearlite on stability of cementite plates - Czarski, Andrzej; Skowronek, Tadeusz; Osuch, Władysław (My University, 2007)
The aim of the studies performed was to assess an influence of crystallographic orientation relationship (OR) between pearlitic ferrite and cementite on a stability of cementite plates. Diffraction analysis made with an electron microscope showed the existence of the Bagaryatski OR and the Pitsch OR both in the pearlite structure after eutectoid transformation and after each tested time of the sphe-roidization annealing. The obtained results indicate that the crystallographic orientation relationship does not influence the stability of cementite showing lamellar morphology.

Celem przeprowadzonych badań była ocena wpływu orientacji krystalograficznej faz perlitu w stali na stabilność płytek cementytu. Analiza dyfrakcyjna wykonana za pomocą mikroskopu elektronowego wykazała występowanie relacji orientacji krystalograficznych Bagariackicgo oraz Pitscha zarówno w strukturze perlitu po przemianie eutektoidalnej, jak i po każdym badanym etapie wyżarzania sferoidyzującego. Otrzymane wyniki badań dyfrakcyjnych wskazują, że na stabilność cementytu wykazującego morfologie płytkową nic wpływa orientacja krystalograficzna cementytu i ferrytu w strukturze wyjściowej.
Wpływ orientacji krystalograficznej faz perlitu na stabilność płytek cementytu
Metallurgy and Foundry Engineering
Keywords: pearlite; spheroidization; perlit; sferoidyzacja; crystallographic orientation relationship; orientacja krystalograficzna